A tale of two deficits: Public budget balance of reserve currency countries - Andreas Steiner (Osnabrück University, Institute of Empirical Economic Research, 2013)
Central banks invest their foreign exchange reserves predominantly in government bonds. The global accumulation of reserves therefore affects the equilibrium in the market for government bonds of reserve currency countries. By means of a panel data analysis we examine the relationship between reserve currency status and public budget balance during different constellations of the international monetary system: the sterling period (1890-1935) and the dollar dominance (since World War II). We show for both periods that reserve currency status significantly lowers the fiscal balance. Any additional dollar of reserves lowers the center's balance by 0.7-1.4 dollars. These novel findings show that reserve currency status increases sovereign debt of the center country.
Keywords: F31; F33; F41; H62; E62; C23; 330; Reserve Currency; Public Balance; International Monetary System; Panel Data Analysis